FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PEMILIK HOMESTAY ATAS LAPORAN KEUANGAN DI DESA WISATA PELAGA - I Gede Dirga Surya Arya Widhydanta; Ni Luh Gde Sari Dewi Astutui (KRISNA: Kumpulan Riset Akuntansi, 2023)
The importance of financial statements with business objectives to be ongoing (going concern), the need for complete financial reports is increasing. Good financial management will ultimately make homestays able to compete and maintain their existence in the tourism industry business. The purpose of this study was to determine the factors that influence financial statement information on homestay owners in Pelaga Tourism Village. The data used in this study are primary data derived from questionnaires distributed to respondents. The sample in this study were homestay owners in Pelaga Tourism Village as many as 35 respondents. The analysis technique used is multiple linear regression. The results research reveals that accounting training, education level, accounting understanding, and the owner's experience has a positive effect on the homestay owner's perception of the financial statements.